A Utility-based Self-Configuration Scheme for Macro-Small Cellular Systems - Li, Cheng-Han; Chen, Jen-Yeu; Chang, Chung-Ju (My University, 2016)
A heterogeneous macro-small cellular network architecture where some small cells are deployed within the coverage of a macrocell is widely considered a promising and practical solution for future 5G wireless communication network. More and more small-cell base stations (SBSs) are deployed in the LTE-A macrocell system to achieve a higher data rate and a better spectrum efficiency. As there could be a large number of SBSs which may together consume a considerable amount of energy, it becomes an important issue to appropriately manage these SBSs for power saving, i.e., to reach a better energy efficiency, upon achieving a certain spectrum efficiency. In this paper, we propose a utility-based self-configuration (USC) scheme in a macro-small cellular system to improve both the spectrum and the energy efficiencies. By the USC scheme, SBSs will adequately switch their operation modes based on a utility function considering both the SBSs\' statuses and user equipment\'s (UE) information. Simulation results show that the proposed USC scheme can achieve better system performances in terms of system throughput and system energy efficiency than a representative SBS power saving scheme in the literature, namely, traffic-aware power saving (TAPS) scheme, and the conventional scheme that all SBSs operate without power saving management.
Keywords: energy efficiency; small cells; heterogeneous cellular networks; operation mode; self-configuration; LTE-A; 5G wireless networks